Common presentation of rare diseases: Left ventricular hypertrophy and diastolic dysfunction - Linhart, Ales; Cecchi, Franco (International journal of cardiology, 2018)
Left ventricular hypertrophy may be a consequence of a hemodynamic overload or a manifestation of several diseases affecting different structural and functional proteins of cardiomyocytes. Among these, sarcomeric hypertrophic cardiomyopathy (HCM) represents the most frequent cause. In addition, several metabolic diseases lead to myocardial thickening, either due to intracellular storage (glycogen storage and lysosomal diseases), extracellular deposition (TTR and AL amyloidosis) or due to abnormal energy metabolism (mitochondrial diseases). The recognition of these rare causes of myocardial hypertrophy is important for family screening strategies, risk assessment, and treatment. Moreover, as there are specific therapies for some forms of HCM including enzyme substitution and chaperone therapies and specific treatments for TTR amyloidosis, a differential diagnosis should be sought in all patients with unexplained left ventricular hypertrophy. Diastolic dysfunction is a key feature of HCM and its phenocopies. Its assessment is complex and requires evaluation of several functional parameters and structural changes. Severe diastolic dysfunction carries a negative prognostic implication and its value in differential diagnosis is limited.
Keywords: amyloidóza; Rare Diseases; hypertrofie levé komory srdeční; Anderson Fabry disease; vzácné nemoci; Ventricular Dysfunction, Left; dysfunkce levé srdeční komory; Danon disease; Hypertrophic cardiomyopathy; Humans; Left ventricular hypertrophy; Amyloidosis; Cardiomyopathy, Hypertrophic; Myocardial storage; hypertrofická kardiomyopatie; Hypertrophy, Left Ventricular; lidé